White blood cell and platelet count as adjuncts to standard clinical evaluation for risk assessment in patients at low probability of acute aortic syndrome. Issue 5 (August 2017) - Morello, Fulvio; Cavalot, Giulia; Giachino, Francesca; Tizzani, Maria; Nazerian, Peiman; Carbone, Federica; Pivetta, Emanuele; Mengozzi, Giulio; Moiraghi, Corrado; Lupia, Enrico
Aims: Pre-test probability assessment is key in the approach to suspected acute aortic syndromes (AASs). However, most patients with AAS-compatible symptoms are classified at low probability, warranting further evaluation for decision on aortic imaging. White blood cell count, platelet count and fibrinogen explore pathophysiological pathways mobilized in AASs and are routinely assayed in the workup of AASs. However, the diagnostic performance of these variables for AASs, alone and as a bundle, is unknown. We tested the hypothesis that white blood cell count, platelet count and/or fibrinogen at presentation may be applied as additional tools to standard clinical evaluation for pre-test risk assessment in patients at low probability of AAS. Methods and results: This was a retrospective observational study conducted on consecutive patients managed in our Emergency Department from 2009 to 2014 for suspected AAS. White blood cell count, platelet count and fibrinogen were assayed during evaluation in the Emergency Department. The final diagnosis was obtained by computed tomography angiography. The pre-test probability of AAS was defined according to guidelines. Of 1210 patients with suspected AAS, 1006 (83.1%) were classified at low probability, and 271 (22.4%) were diagnosed with AAS. Within patients at low probability, presence of at least one alteration among white blood cell count >9*10 3 /µl, platelet count <200*10 3 /µl and fibrinogen <350 mg/dl was associated with a sensitivity of 95.5% (89.7–98.5%) and a specificity of 18.3% (15.6–21.2%). In patients at low probability, white blood cell count >9*10 3 /µl and platelet count <200*10 3 /µl were found as independent predictors of AAS beyond established clinical risk markers. Within patients at low probability, the estimated risk of AAS based on the number of alterations amongst white blood cell count >9*10 3 /µl and platelet count <200*10 3 /µl was 2.7% (1.2–5.7%) with zero alterations, 11.3% (8.8–14.3%) with one alteration and 31.9% (24.8–40%) with two alterations ( p <0.001). Conclusion: In addition to standard clinical evaluation, white blood cell count and platelet count may be used in patients at low pre-test probability to fine-tune risk assessment of AAS.